Noncontiguous finished genome sequence and description of Bacillus testis strain SIT10 sp. nov. (July 2016) - Cimmino, T.; Traore, S.I.; Valentini, C.; le Page, S.; Sokhna, C.; Diallo, A.; Raoult, D.; Rolain, J.M.
Abstract: Bacillus testis strain SIT10 (= CSUR P1492 = DSMZ 101190) is the new type strain collected from stool from a 2-year-old boy from Senegal during a culturomics study. This Gram-positive bacterium is a facultative anaerobic rod and a member of the Bacillaceae family. We describe here the features of this bacterium, together with the complete genome sequence and annotation. The 3 987 349 bp long genome (one chromosome but no plasmid) with 42.8% GC content contains 4005 protein-coding and 171 sRNA genes, including 19 5S rRNA gene, 15 16S rRNA genes and ten 23S rRNA genes.